2008
DOI: 10.1111/j.1365-2044.2008.05486.x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal mask airway and tracheal tube cuff pressures in children: are clinical endpoints valuable for guiding inflation?

Abstract: SummaryWe prospectively assessed common clinical endpoints for their usefulness in avoiding hyperinflation of the cuffs of laryngeal mask airways (slight outward movement) and tracheal tubes (disappearance of an audible leak around the cuff during manual ventilation < 20 cmH 2 O) in 640 children. Cuff pressures were measured at induction and immediately before emergence from anaesthesia. With the laryngeal mask airway (sizes 1-4), the median cuff pressures ranged from 90 to > 120 cmH 2 O at induction and 105 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 36 publications
4
47
1
3
Order By: Relevance
“…Furthermore, the results of the present study show that particular care has to be taken in smaller sized LMs since small volume changes can cause large changes in intra-cuff pressure. Particular care should be taken when nitrous oxide is used, because diffusion into the LM cuff is associated with a significant increase in LM cuff pressure [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of the present study show that particular care has to be taken in smaller sized LMs since small volume changes can cause large changes in intra-cuff pressure. Particular care should be taken when nitrous oxide is used, because diffusion into the LM cuff is associated with a significant increase in LM cuff pressure [9].…”
Section: Discussionmentioning
confidence: 99%
“…Increased intracuff pressure, as well as the use of intermittent positive pressure ventilation, could affect laryngeal soft tissue [20,21], and Tanaka et al [12] have shown depression of defensive reflexes over a period of time when an LMA is in situ. However, the measurements in our study were performed immediately following induction of anaesthesia; care was taken to apply low cuff pressures [22] and all patients were breathing spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to determine the optimal insertion technique as unsuccessful prolonged insertion and multiple attempts may lead to adverse events in patients. For safe and easy insertion of LMA following items should be noticed: appropriate size, partially inflated cuff [16][17][18] and a skilled person [8].The success rate of first attempt insertion using standard Brain technique is almost 79-93% [7;19-22]. Hence, many alternative techniques like rotational or reverse, fully or partially inflated cuff, change of head position, laryngoscopic guided, lateral, use of introducer and Yodfat technique have been described to improve the success rate of LMA insertion.…”
Section: Many Anesthesiologists Do Not Use the Brain Technique Properlymentioning
confidence: 99%